Diminished creatinine clearance in anorexia nervosa: reversal with weight gain. Issue 1 (January 1985) - Boag, F; Weerakoon, J; Ginsburg, J; Havard, C W; Dandona, P
Abstract : To assess whether patients with anorexia nervosa have abnormalities in creatinine clearance, we measured plasma creatinine concentration, urinary creatinine excretion, and creatinine clearance in 10 patients with anorexia nervosa before and during treatment. Urinary creatinine excretion and creatinine clearance were diminished in all patients. Nine patients had significant decreases in their plasma creatinine and creatinine clearance was increased even when corrected for body weight and body surface area respectively. The patient who did not show these changes in plasma creatinine concentration and creatinine clearance had gained only 4% in body weight. Body weight and corrected creatinine clearance were significantly correlated, as were percentage increases in body weight and creatinine clearance. Thus anorexia nervosa is associated with a reversible decrease in creatinine clearance. Increase in body weight appears to be cardinal to the recovery of renal function in these patients.